KẾT CẤU VÀ ĐA DẠNG LOÀI CÂY GỖ Ở RỪNG ẨM NHIỆT ĐỚI TẠI VƯỜN QUỐC GIA CÁT TIÊN - Vũ, Mạnh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STRUCTURE AND DIVERSITY OF WOOD PLANT IN TROPICAL MOIST FOREST IN CAT TIEN SOUTH AREA IN CAT TIEN NATIONAL PARK, DONG NAI PROVINCE Study and analyze the structure of tree species and tree species diversity of tropical moist forests in Nam Cat Tien area in Dong Nai province. The structure and diversity of tree species of this forest type were analyzed from 15 typical sample plots with the size of 0.25 ha. The study results indicated that the total number of tree species encountered in the 15 sample plots or 3.75 ha of tropical moist forest in Nam Cat Tien area was 75 species belonging to 56 genera of 31 families. The dominant tree family is Dipterocarpaceae (IVI index = 26.0%), 6 co-dominant families (Myrtaceae, Sapindaceae, Lythraceae, Ebenaceae, Clusiaceae and Verbenaceae) contributed 36.7%. Other families contributed only 37.3% in density, number of species and cross-section. This forest type has 7 dominant and co-dominant species. They contribute 43.3% in density, cross section and wood volume; the highest is Hopea odorata (IVI = 8.6%), the lowest is Dipterocarpus dyeri (IVI = 4.1%). This type of forest encounters 8 tree species of the Dipterocarpaceae family; in which Hopea odorata has the largest ecological role (IVI = 8.6%), followed by Shorea guiso (IVI = 7.1%), the lowest is Shorea roxburghii (IVI = 0.4%). The tropical moist forest type in the study area is a rich ecosystem of families and tree species. The rich index on them (d-Margalef) and the tree species respectively are 3.5 and 5.3. The homogeneous indexes on the family (J ’) and the corresponding tree species are 0.80 and 0.82. The family diversity index (H ’) and tree species diversity are 2.33 and 2.73 respectively. Simpson’s dominant index (1 - λ) in the family and tree species are 0.86 and 0.90. The distribution of tree species is uneven in space (- Whittaker index = 2.7). In general, the diverse family and tree species of tropical moist forests in the study area receive moderate values (H ’ = 2 - 3).